Relative Efficiency of Brown Sugar Agroindustry in Kokap District, Kulon Progo Regency, D.I. Yogyakarta - Dian Eswin Wijayanti; Slamet Hartono; Dwidjono Hadi Darwanto (Agro Ekonomi, 2016)
Agriculture industry is the activity using agriculture product as raw material by further process become the result product and is conducted by packaging, saving to the distributor toward consumer. Coconut (Cocos Nucifera) is one of agriculture commodity that has good potential market in Kulon Progo. Besides sold as a fresh product, coconut tree also produced nira (liquid from palm tree) that is quite potential if it is further process become brown sugar (brown sugar) to increase economic value from the characteristic of agriculture commodity. Thus, agriculture industry in that region could overcome the weaknesses of agriculture product through efficient production. The efficiency of production is obtained if input and output is used optimally so that it is able to give the advantage for agent of agriculture industry. This research is aimed to (1) analyze production efficiency of brown sugar agriculture industry, (2) to analyze external factors which affecting production efficiency of brown sugar. Basic research method which is quantitative approach supported by qualitative approach. The research is conducted in sub-district of Kokap, Kulon Progo, Yogyakarta with 100 respondents that is randomly chosen. Data of production efficiency on agriculture industry of brown sugar is obtained through Data Envelopment Analysis (DEA) by classifying into 30 Decision Making Unit (DMU). The classification is conducted based on the amount of raw material which used, while linier regression is using for Ordinary Least Square (OLS) that is used to analyze external factors which affect production efficiency on  agriculture industry of brown sugar. The result of research shows that the production on agriculture industry of brown sugar is more inefficient that is 28 DMU (93,33%) and the efficient production is only 2 DMU (6,67%). The external factor affected toward efficiency of agriculture industry production of brown sugar are the age of farmer, the experience of flow quickly, and the amount of coconut tree for nira.